Psychosocial issues of newly diagnosed gynaecological cancer patients: a qualitative study - Koroth, Ramesan Chiyancheri; Thomas, Anitha; Ravindran, Vinitha; Peedicayil, Abraham; Thomas, Vinotha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The diagnosis of cancer generates significant anxiety and uncertainty. We aimed to identify the psychosocial needs and priorities of women newly diagnosed with gynaecological cancers. Methods: The study employed a qualitative research design. In-depth interviews were conducted with patients and their attendants to explore their anxieties, information needs, expectations, and treatment priorities. After obtaining informed written consent, 16 patients were included. Data analysis was performed through conventional qualitative content analysis, following a descriptive-explorative approach. This process involved extracting codes, categories, and themes to better understand the patients’ experiences. Results: The content analysis of the transcripts brought forth five themes: 1) cause of cancer and its effects, 2) information needs and expectations, 3) concerns about prognosis and family, 4) dependence versus independence and 5) faith and hope in God. In our setting, patients with gynaecological cancer had low information needs regarding their disease stage and treatment options. They trusted their healthcare providers and preferred not to burden themselves with potentially distressing information. They sought information on prognosis and the chance of cure. Concerns about finances and daily living were prevalent, while worries about sexual activity were less common. Spiritual issues affected many and included despondency and faith in God. Conclusions: Understanding patients’ information needs and anxieties will enhance their care and treatment adherence.